Impact of surgical infrastructure and personnel on volume and availability of essential surgical procedures in Liberia. Issue 6 (18th September 2020) - Adde, H A; Duinen, A J; Oghogho, M D; Dunbar, N K; Tehmeh, L G; Hampaye, T C; Salvesen, Ø; Weiser, T G; Bolkan, H A
Abstract: Background: Essential surgical procedures rank among the most cost-effective of all healthcare interventions. The aim of this study was to enumerate surgical volumes in Liberia, quantify surgical infrastructure, personnel and availability of essential surgical procedures, describe surgical facilities, and assess the influence of human resources and infrastructure on surgical volumes. Methods: An observational countrywide survey was done in Liberia between 20 September and 8 November 2018. All healthcare facilities performing surgical procedures requiring general, regional or local anaesthesia in an operating theatre between September 2017 and August 2018 were eligible for inclusion. Information on facility infrastructure and human resources was collected by interviewing key personnel. Data on surgical volumes were extracted from operating theatre log books. Results: Of 70 healthcare facilities initially identified as possible surgical facilities, 52 confirmed operative capacity and were eligible for inclusion; all but one shared surgical data. A national surgical volume of 462 operations per 100 000 population was estimated. The median hospital offered nine of 26 essential surgical procedures. Unequal distributions of surgical infrastructure, personnel, and essential surgical procedures were identified between facilities. In multivariable regression analysis, surgical human resources (β = 0·60, 95 per cent c.i. 0·34 to 0·87; P < 0·001) and infrastructure (β = 0·03, 0·02 to 0·04; P < 0·001) were found to be strongly associated with operative volumes. Conclusion: The availability of essential surgical procedures in Liberia is extremely low. Descriptive tools can quantify inequalities, guide resource allocation, and highlight rational investment areas. Graphical Abstract: The availability of essential surgical procedures in Liberia is extremely low. Quantifying surgical infrastructure, surgical personnel and essential surgical procedures can guide resource allocation and highlight rational investment areas. Surgical needs clearly identified